Business Disruptions Due to Social Vulnerability and Criminal Activities in Urban Areas - Nick Drydakis (Global Labor Organization (GLO), 2024)
This study investigates the relationship between social vulnerability, illegal activities, and location-based business disruptions in Athens, the capital of Greece. The research utilises repeated cross-sectional data from 2008, 2014, and 2023, gathered from areas with high levels of criminal activity, reflecting the experiences of business owners and managers in these locations. The findings reveal that heightened levels of social vulnerability-including the presence of illicit drug users and homeless individuals-alongside illegal activities such as gang-related protection rackets and black-market operations, are associated with increased location-based business disruptions. These disruptions manifest in assaults on employees and customers, business burglaries, reputational damage, supply chain problems, and decreased turnover. The study also examines the impact of economic conditions in 2014 and 2023, when Greece's Gross Domestic Product was lower than in 2008, indicating an economic recession. The findings suggest that the economic downturn during these years further exacerbated location-based business disruptions. Conversely, enhanced public safety measures, such as increased police presence, law enforcement, and improved public infrastructure, were associated with a reduction in these disruptions. Furthermore, an interesting insight was that businesses with longer operating histories tend to experience fewer location-based disruptions, indicating that operating history might be perceived as a resilience factor. The study suggests that policy actions should focus on increasing police visibility, providing financial support to high-risk businesses, funding urban regeneration projects, maintaining public infrastructure, and delivering social services aimed at helping marginalised communities escape vulnerability.
Keywords: K4; K42; L26; I3; E32; 330; Social Vulnerability; Illegal Activities; Crime; Criminality; Business; Entrepreneurship; Business Disruptions; Economic Recessions; Public Safety